MANAJEMEN LEMBAGA PENGEMBANGAN TILAWATIL QUR’AN DKI JAKARTA DALAM MEMPERSIAPKAN KUALITAS CALON DUTA PESERTA MTQ DAN STQ - Mujawwid, Mochamad; Sastradiharja, EE Junaidi; Shunhaji, Akhmad (el-Moona: Jurnal Ilmu Pendidikan Islam, 2024)
This study examines the management strategy of LPTQ DKI Jakarta in preparing prospective ambassadors for MTQ/STQ participants. To produce credible research findings, this research uses qualitative methodological tools, where data is collected based on the results of observations, interviews and documentation. The results of the study show that LPTQ DKI Jakarta implements three main strategies, namely the planning, organizing and implementation stages. Planning includes the recruitment of participants from the village level to the mayor level through coaching centers. Organizing involves the establishment of an administrative structure at each level and the selection of the best participants to be trained at the provincial level. The implementation stage includes advanced level coaching through continuous training and intensive quarantine. In addition, improving the quality of participants is carried out through long-term recruitment, talent guidance, and intensive coaching. LPTQ DKI Jakarta's significant contribution can be seen in the achievement of national achievements, which are fully supported by the provincial government through grant funding. This management program not only has an impact on improving the quality of participants in DKI Jakarta, but also provides input for the implementation of MTQ at the national level.